Vietnam and countries of the Mekong - Henderson, Larry Wills (Nashville, Canada : Thomas Nelson, 1972)
A profile of five countries that share a common Indo-Chinese culture--Vietman, Laos, Cambodia, Thailand, Burma--emphasizing the cultural and geographic background of each as well as their political and economic struggles.
Bibliography: p. 245.
Keywords: Asia, Southeastern -- Juvenile literature